O inconsciente no jovem Nietzsche: da intencionalidade das formas naturais à vida da linguagem - William Mattioli (2016)
The goal of this study is to analyze the genesis and development of the notion of the unconscious in Nietzsche based on the reading of some early texts from the period between 1867 and 1873. Our starting point is the thesis that the concept of "Dionysian presented in The Birth of Tragedy constitutes a metaphor for the unconscious full of nuances and layers. In a sense, this notion can be seen as the culmination point of a series of reflections elaborated by Nietzsche in previous years andat the same time as the matrix from which he will develop in his subsequent work some of his main theories and hypotheses. The reflections previous to The Birth of Tragedy to which we refer are theresult of the convergence of diverse sources and influences with which Nietzsche had contact in his formative years and derive especially from a confrontation with certain aspects of the post-Kantian transcendental philosophy and its relationship with some theories of what may be called speculative biology of the second half of the nineteenth century. We intend to follow the development of the notion of unconscious in the young Nietzsche from that cluster of sources and influences. The thread of our analysis is the notion of "unconscious intentionality", with which, according to the hypothesis of this work, the philosopher approaches certain positions that can be qualified as panpsiquist and vitalist.